2013
DOI: 10.1103/physrevlett.110.195003
|View full text |Cite
|
Sign up to set email alerts
|

Approaching the Theoretical Limit of Diamagnetic-Induced Momentum in a Rapidly Diverging Magnetic Nozzle

Abstract: Cross-field diffusion and plasma expansion in a rapidly diverging magnetic nozzle are controlled while maintaining constant plasma production in a contiguously attached radio frequency plasma source. It is demonstrated that the measured electron-diamagnetic-induced axial momentum increases with increasing magnetic field strength to approach the theoretical limit derived using an ideal nozzle approximation. The measured axial momentum exerted onto the axial and radial plasma source boundaries validate the predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
109
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(127 citation statements)
references
References 15 publications
18
109
0
Order By: Relevance
“…Although the radial loss of ions is important in the continuity equation, these ions carry only a small momentum with them, so that the radial momentum losses have been ignored as well. These momentum losses have recently been directly measured experimentally 49 and found to be small. Combining Eqs.…”
Section: Axial Plasma Variationmentioning
confidence: 95%
“…Although the radial loss of ions is important in the continuity equation, these ions carry only a small momentum with them, so that the radial momentum losses have been ignored as well. These momentum losses have recently been directly measured experimentally 49 and found to be small. Combining Eqs.…”
Section: Axial Plasma Variationmentioning
confidence: 95%
“…This basic electromagnetic thrust force is lower than the other helicon plasma sources [12][13][14][15]24) . The dimensions of our helicon plasma source are smaller diameter and longer length than the other helicon plasma sources.…”
Section: Resultsmentioning
confidence: 73%
“…These studies report that the detail plasmadynamics and the thrust production mechanism by the magnetic nozzle. Takahashi et al separately measured the electromagnetic thrust force and the thermal thrust force produced by the magnetic nozzle, and confirmed the magnetic nozzle theory [12][13][14][15] . The previous researches indicated that the plasma pressure (electron pressure) has to be increased for higher thrust force, and stronger magnetic field is needed to confine higher plasma pressure.…”
Section: Introductionmentioning
confidence: 75%
“…[7][8][9] Some of them are operated under externally applied magnetic fields contributing to plasma confinement, 10 spontaneous plasma acceleration, 11,12 control of spatial profile of the charged particles, 13,14 and filtering an energetic electrons. 3,6,15,16 When applying the external magnetic field to the rf plasmas driven by the frequency much less than an electron cyclotron frequency, it is also well known that a high density plasma can be obtained due to a wave heating and a resultant ionization process, being called a helicon wave discharge.…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous studies, the thrust components corresponding to the pressure inside the source and the Lorentz force in the magnetic nozzle originates from the electron pressure. 12,24,25 Therefore the exhaust of the energetic electrons seems to contribute to enhancement of the propulsion performance due to the exhaust of the energy from the system, while it causes the non-uniform profiles of the electron temperature and the densities of both the charged particles and the uncharged species downstream of the source. In the rf hydrogen/deuterium negative ion source, a transverse magnetic field is also applied near a beam a kazunori@ecei.tohoku.ac.jp extraction grid system to reduce the electron temperature, where the non-axisymmetric magnetic field profile induces the drift of the charged particles and the resultant non-uniform density profiles of the plasma and the beam.…”
Section: Introductionmentioning
confidence: 99%